Could the Icelandic banking collapse of 2008 have been prevented? The role of economists prior to the crisis - John S.L. McCombie; Marta R.M. Spreafico (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
In 2008, the three main banks in Iceland collapsed. There is strong evidence that the banks would have become insolvent even without the subprime crisis. Yet there was a marked difference in opinion at the time about the viability of the Icelandic banks. A clean bill of health was given by the commissioned reports of Mishkin in 2007 and Portes in 2008, just prior to the collapse, whereas severe reservations about the Icelandic financial system were expressed by Wade, inter alios. These contrasting views were widely debated and may well have influenced both potential and actual foreign depositors in the banks. This paper analyses the disparate arguments put forward and contrasts it with the actual outcome. It considers the influence of economists in public policy debates and draws some methodological conclusions.
Keywords: A11; E6; G00; 330; 2008 Icelandic banking crisis; financial regulation; rating agencies; role of economists; Special Investigation Commission